Longitudinal pathways of exclusive and polytobacco cigar use among youth, young adults and adults in the USA: findings from the PATH Study Waves 1–3 (2013–2016). (22nd April 2020) - Edwards, Kathryn C; Sharma, Eva; Halenar, Michael J; Taylor, Kristie A; Kasza, Karin A; Day, Hannah; Hammad, Hoda T; Anic, Gabriella; Bansal-Travers, Maansi; Limpert, Jean; Gardner, Lisa D; Borek, Nicolette; et al.
Abstract : Objective: The goal of this study is to examine the cross-sectional prevalence of use and 3-year longitudinal pathways of cigar use in US youth (12-17 years), young adults (18-24 years), and adults 25+ (25 years or older). Design: Data were drawn from the first three waves (2013–2016) of the Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal cohort study of US youth and adults. Respondents with data at all three waves (youth, n=11 046; young adults, n=6478; adults 25+, n=17 188) were included in longitudinal analyses. Results: Weighted cross-sectional prevalence of past 30-day (P30D) use was stable for adults 25+ (~6%), but decreased in youth (Wave 1 (W1) to Wave 3 (W3)=2.5% to 1.2%) and young adults (W1 to W3=15.7% to 14.0%). Among W1 P30D cigar users, over 50% discontinued cigar use (irrespective of other tobacco use) by Wave 2 (W2) or W3. Across age groups, over 70% of W1 P30D cigar users also indicated P30D use of another tobacco product, predominantly cigar polytobacco use with cigarettes. Discontinuing all tobacco use by W2 or W3 was greater in adult exclusive P30D cigar users compared with polytobacco cigar users. Conclusions: Although the majority of P30D cigar users discontinued use by W3, adult polytobacco users of cigars were less likely to discontinue all tobacco use than were exclusive cigar users. Tracking patterns of cigar use will allow further assessment of the population health impact of cigars.